The Effect of Baby Gym on Improving Baby Development in Purwakarta Regency, Indonesia - Desty Budi Lestari; Lova, Nova Rati (HM Publisher, 2024)
Introduction: Infancy is a critical period for physical, cognitive, and social-emotional development. Baby gym is a stimulation program designed to improve baby development through various physical, sensory, and social activities. This research aims to analyze the effectiveness of baby gym in improving baby development in Purwakarta Regency, Indonesia. Methods: Quasi-experimental research design with pre-test and post-test. A sample of 60 babies aged 6-12 months was divided into two groups: intervention (n=30) who participated in the baby gym program for 3 months and controls (n=30) who did not participate in the baby gym program. Infant development was measured using the Denver developmental screening test (DDST) before and after intervention. Results: There was a significant difference in the development of babies in the intervention group compared to the control group (p<0.05). The intervention group showed a higher increase in the DDST total score and gross motor, fine motor, language, and personal social subdomains. Conclusion: The baby gym program is effective in improving baby development in Purwakarta Regency, Indonesia.